2022
DOI: 10.2174/1573396318666220304210653
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cerebral Oxygen Saturation Monitoring on Short-term Neurodevelopmental Outcomes in Neonates with Encephalopathy - A Prospective Cohort Study

Abstract: Background: Near-infrared spectroscopy (NIRS) has been applied for cerebral oxygen saturation (rSO2) monitoring in neonates. There is a paucity of data from low-middle income countries (LMIC) setting of cerebral rSO2 in neonates with encephalopathy of diverse etiologies. This study aimed to monitor cerebral rSO2 using NIRS in encephalopathic neonates aiming to maintain the rSO2 between 55 to 85%, in the first 72 hours of admission in order to improve short-term neurodevelopmental outcomes (NDO). Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Lemmers et al21 noted that healthy infants would maintain their rScO 2 within a documented neuroprotective range of approximately 55% to 85% 21. A similar range was also documented in a study of 120 infants with varying degrees of encephalopathy 17. This study reported that sustaining an rScO 2 between 55% and 85% within the first 72 hours of life was associated with improved neurodevelopmental outcomes 17.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Lemmers et al21 noted that healthy infants would maintain their rScO 2 within a documented neuroprotective range of approximately 55% to 85% 21. A similar range was also documented in a study of 120 infants with varying degrees of encephalopathy 17. This study reported that sustaining an rScO 2 between 55% and 85% within the first 72 hours of life was associated with improved neurodevelopmental outcomes 17.…”
Section: Discussionmentioning
confidence: 68%
“…21 A similar range was also documented in a study of 120 infants with varying degrees of encephalopathy. 17 This study reported that sustaining an rScO 2 between 55% and 85% within the first 72 hours of life was associated with improved neurodevelopmental outcomes. 17 rScO 2 trends of term newborns shortly after birth document an average rScO 2 of 77.9% ± 8.5%.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations